Study on mechanical and energy characteristics of coal samples under different unloading states - Meng, Jianbing; Jiao, Xianjun; Gao, Song; Zhu, Xiangbin; Cheng, Shuangli; Zhou, Wei (Frontiers in Earth Science, 2023)
There are many types of coal seams in China, and the mining of protective layers will cause different rates of stress reduction in protected coal seams at different intervals. Therefore, experiments were conducted at different unloading rates to explore the strength, deformation, and energy characteristics of coal. Research findings: the AE (acoustic emission) signal of the coal body before unloading has a small range of changes and similar characteristics. After unloading begins, because of the different development rates of internal crack in the coal body under different unloading states, the AE signal of the coal body varies at different unloading rates. The maximum stress increases exponentially with the increase of unloading rate. It was found that the higher the unloading rate, the easier and earlier the coal sample is to be damaged. And it was discovered that the dissipated energy of the coal sample in the elastic stage is extremely low, and a large amount of total energy is converted into elastic energy and stored inside the coal sample. The dissipation energy increases during the plastic stage, while the trend of increasing elastic energy slows down. After the peak stage, the dissipated energy rapidly increases and the elastic energy decreases.